Pengaruh Disiplin Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pada Tauch Terminal Resort Tulamben - Dewi, Ni Komang Ary Apriliana; Suryaningsih, Ida Ayu Anggreni; Sari, Ni Luh Komang Julyanti Paramita (Jurnal Mosaik Hospitaliti, 2024)
This study was conducted with the aim to determine the effect of work discipline and compensation on employee performance at Tauch Terminal Resort Tulamben. The type of research conducted is quantitative research by distributing questionnaires to employees at Tauch Terminal Resort Tulamben. The number of samples used in this study were 51 respondents, namely all employees at Tauch Terminal Resort Tulamben. The distribution of questionnaires or questionnaires using a 5-point Likert scale measurement. Tests carried out include reliability and validity tests, classical assumption tests consisting of normality tests, multicolonierity tests and heteroscedasticity tests. The analysis carried out through the Multiple Linear Regression test, the Determination coefficient test, and the Hypothesis Test consisting of the t test and the F test. The results of this study indicate that the work discipline coefficient value of 0.487 has a positive effect on employee performance, the compensation coefficient value of 0.661 has a positive effect on employee performance and 64.8% of the independent variables have an influence on the dependent variable. Thus, it is concluded that Work Discipline and Compensation partially and simultaneously affect employee performance at Tauch Terminal Resort Tulamben.